Regorafenib alone or in combination with high/low-dose radiotherapy plus toripalimab as third-line treatment in patients with metastatic colorectal cancer: protocol for a prospective, randomized, controlled phase II clinical trial (SLOT) - Zhou, Shujuan; Wang, Chenchen; Shen, Lijun; Wang, Yan; Zhang, Hui; Wu, Ruiyan; Wang, Yaqi; Chen, Yajie; Xuan, Yan; Xia, Fan; Zhang, Zhen; Wan, Juefeng (Frontiers in Oncology, 2023)
Combination strategies to improve immunotherapy response in microsatellite stable metastatic colorectal cancer (MSS mCRC) remain an unmet need. Several single-arm clinical trials have shown promising synergistic effects between regorafenib and ICIs; however, some contradictory results have also been reported. Randomized controlled trials are needed to further validate the combination of regorafenib with ICIs. In addition, low-dose radiotherapy has been demonstrated to induce local immune responses by reprogramming the tumor microenvironment when combined with high-dose radiotherapy and ICIs. In this study, we designed a prospective, randomized, controlled phase II trial to investigate the efficacy and safety of regorafenib in combination with high/low-dose radiotherapy plus toripalimab in MSS mCRC compared to regorafenib alone. Patients with MSS metastatic adenocarcinoma of the colon or rectum will be enrolled and randomly assigned into two arms: a control arm and an experimental arm. Patients in the control arm will receive regorafenib monotherapy (120 mg once daily on days 1-21 of each 28 days cycle). Patients in the experimental arm will first receive one cycle of regorafenib (80 mg once daily on days 1-21 of each 28 days cycle) and toripalimab (240mg, q3w), followed by high-dose (4-8 fractions of 8-12Gy) and low-dose (1-10Gy at 0.5-2Gy/fraction) radiotherapy, and then continue regorafenib and toripalimab treatment. The primary endpoint is the objective response rate, and the secondary endpoints are disease control rate, duration of remission, median progress-free survival, median overall survival, and adverse events. Recruitment started in August 2023 and is ongoing. Clinical Trial Registration https://clinicaltrials.gov/study/NCT05963490?cond=NCT05963490&rank=1, identifier NCT05963490.